2003
DOI: 10.1016/j.neuron.2003.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization-Induced Ca2+ Release in Ischemic Spinal Cord White Matter Involves L-type Ca2+ Channel Activation of Ryanodine Receptors

Abstract: The mechanisms of Ca(2+) release from intracellular stores in CNS white matter remain undefined. In rat dorsal columns, electrophysiological recordings showed that in vitro ischemia caused severe injury, which persisted after removal of extracellular Ca(2+); Ca(2+) imaging confirmed that an axoplasmic Ca(2+) rise persisted in Ca(2+)-free perfusate. However, depletion of Ca(2+) stores or reduction of ischemic depolarization (low Na(+), TTX) were protective, but only in Ca(2+)-free bath. Ryanodine or blockers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
185
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(203 citation statements)
references
References 49 publications
16
185
2
Order By: Relevance
“…The immediate rise in calcium after injury and our EGTA experiments suggested an extracellular source of calcium. Therefore, we performed a series of pilot experiments that pharmacologically queried established molecularly defined entry pathways (for example, voltage-gated calcium channels [17][18][19] ; reverse action of the sodium-calcium exchanger [20][21][22] ; glutamate receptors 23 ). These experiments failed to show strong effects on initial calcium rises (proportion of calcium-elevated axons at initial p.i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The immediate rise in calcium after injury and our EGTA experiments suggested an extracellular source of calcium. Therefore, we performed a series of pilot experiments that pharmacologically queried established molecularly defined entry pathways (for example, voltage-gated calcium channels [17][18][19] ; reverse action of the sodium-calcium exchanger [20][21][22] ; glutamate receptors 23 ). These experiments failed to show strong effects on initial calcium rises (proportion of calcium-elevated axons at initial p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Given the critical role of calcium accumulations in contused axons, it is important to consider where the intra-axonal calcium is coming from and which downstream mechanisms it initiates. In vitro and in a multitude of neurological conditions, including trauma, ischaemia, inflammation and degeneration 12,26 , a broad range of mechanisms have been implicated as sources for elevated axonal calcium, including extracellular sources (for example, voltage-gated ion channels [17][18][19] , the plasma membrane sodiumcalcium exchanger [20][21][22] , the acid sensing ion channel 27 or nodal glutamate receptors 23 ), as well as intracellular stores (such as mitochondria 28 or the endoplasmic reticulum 29 ). Our in vivo analysis now indicates that mechanoporation, that is, the formation of pores in the plasma membrane as first described after diffused brain injury 24 , is a dominant source of calcium influx at least in the first hours after contusion.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, it was known that only RyR-1, known as the skeletal muscle isoform, does not require an influx of extracellular Ca 2+ for its activation and that RyR-1 is co-immunoprecipitated with the α 1c subunit. The latter provides direct evidence for functional coupling between these two proteins (27). That is, surface membrane depolarization sensed by Ltype VGCCs is transduced to activate RyR-1.…”
Section: Sal Cocamentioning
confidence: 86%
“…We examined how the blockade of L-type VGCCs by nifedipine affected the increased expression of these RyRs because our previous study demonstrated that Ltype VGCC blockers inhibited the development of the rewarding effect of METH (9) and there is functional interaction between L-type VGCCs and RyRs known as CICR (27). Nifedipine pre-administered i.c.v.…”
Section: Effect Of Nifedipine On Increase In Ryr-1 and -2 Expression mentioning
confidence: 99%
“…For example, cardiac DHPRs (Ca V 1.2), as well as Ca V 1.3, but not skeletal DHPRs (Ca V 1.1), in brain coimmunoprecipitate RyR1 [36]. In spinal cord white matter, Ca V 1.2 co-immunoprecipitates RyR1, while Ca V 1.3 precipitates RyR2, and functional evidence is presented suggesting an external Ca 2+ -independent coupling process like that in skeletal muscle [37]. These observations have led to suggestions of functional depolarization-dependent coupling between the cardiac DHPR and RyR1 in the central nervous system.…”
Section: Interactions Between Dhprs and Ryrsmentioning
confidence: 88%